Morphology and molecular characterization of Ceratomyxa sp. (Cnidaria, Myxosporea, Ceratomyxidae), infecting the gallbladder of Curimata cyprinoides (Characiformes: Curimatidae) in the lower Araguaia River, Brazil - Maria Josinete Araujo Costa; Maria Queroz Carneiro Silva; Marcelo Francisco da Silva; Evonnildo Costa Gonçalves (Revista Brasileira de Parasitologia Veterinária)
Abstract This study reports the occurrence of a myxosporid parasite of the genus Ceratomyxa Thélohan, 1892 found in the gallbladder of Curimata cyprinoides Linnaeus, 1766. This species is abundant in the Tocantins-Araguaia hydrographic basin and holds environmental, social and economic importance. The genus Ceratomyxa is characterized by two equally-sized polar capsules with lateral projections, whick may appear slightly slightly arched in a half-moon shape or fully curved arched. Light microscopy and molecular analysis were employed in this study. The mature spores were composed of two equally-sized symmetrical valves with equal capsular foramina and two equally-sized lateral projections. These spores (n=40) were freely suspended in the gallbladder, with a total length of 11.2 ± 0.1 μm and width of 4.0 ± 0.3 μm. The polar capsules measured 2.1 ± 0.1 μm in both length and width; and the two symmetrical lateral elongations formed a posterior angle of 41.4º ± 0.7º. An integrated comparative analysis of the morphological characteristics and partial SSU rDNA sequences confirmed this finding as a parasite of the genus Ceratomyxa sp., located in the gallbladder of C. cyprinoides in the Tocantins-Araguaia basin, within the municipality of Araguatins, in eastern Amazon, Brazil.